PENGARUH LOKASI DAN FASILITAS TERHADAP KEPUASAN PENGUNJUNG DI PANORAMA PABANGBON LEUWILIANG BOGOR - Lenny Yusrini; Rizmaulida Triandini (LPPM and Travel Operation Department Universitas Asa Indonesia, 2018)
The purpose of this study was to know and analyze the influence of the location and facilities of the tourist attraction towards visitor’s satisfaction. The study is a survey using a questionnaire developed by the underlying theories of location and facilities of tourist attraction. In the early stage, validity and reliability tests were conducted and the test results showed all items are valid. The questionnaires then were distributed to the respondents using simple random sampling technique involving 100 respondents. The analytical method used is multiple linear regression with the help of the SPSS version 20.00 software. The result showed the significance score is 0,000 < 0,05 which means that both location and facilities have significant influence towards customer satisfaction